GLASS CEILING IN THE WORLD OF WORK (Burhani Epistemology Perspective) - Alif Nur Fitriyani; Achmad Khudori Soleh (Islamuna: Jurnal Studi Islam, 2022)
In addition to discrimination, the lack of respect for women’s skills and the difficulty of women to get and achieve positions equal to or even higher than men in the world of work make many women tend to stay at home and refuse to enter the labor market. The purpose of this research is that women avoid the glass ceiling from a rational Burhani perspective in the contemporary era and not be studied only by textual studies. The research method used is descriptive analysis with Burhani epistemological syllogism, which is reviewed by literature from books, journals, and literature so that it uses a qualitative approach in the results. The results of the study state that the Glass ceiling phenomenon for women in the world of work is the influence of factors that still uphold patriarchy and only see it from the perspective of the text. In contrast to Burhani who uses reason (ratio). He views that women also have the same rights and share in the work and position of women in the world of work according to their abilities. The implication of this research is leadership, a taboo subject, and even other positive things that are not found in the leadership or performance of men. So that there will be other women who become leaders in the era of modernization in various fields of work. ABSTRAK Selain diskriminasi, kurangnya penghargaan terhadap keterampilan perempuan dan sulitnya perempuan untuk mendapatkan dan mencapai posisi yang sama atau bahkan lebih tinggi dari laki-laki di dunia kerja membuat banyak perempuan cenderung tinggal di rumah dan menolak memasuki pasar kerja. Tujuan dari penelitian ini adalah agar perempuan terhindar dari glass ceiling dipahami dari perspektif burhani secara rasional di era kontemporer dan tidak hanya dikaji dengan kajian tekstual. Metode penelitian yang digunakan adalah deskriptif analisis dengan silogisme epistimologi burhani, yang dikaji secara kepustakaan dari buku, jurnal, dan literatur sehingga menggunakan pendekatan kualitatif dalam hasilnya. Hasil penelitian menyatakan bahwa fenomena Glass ceiling bagi perempuan di dunia kerja merupakan pengaruh dari faktor-faktor yang masih menjunjung tinggi patriarki dan hanya melihatnya dari perspektif teks. Berbeda dengan Burhani yang menggunakan akal (rasio). Ia memandang bahwa perempuan juga memiliki hak dan andil yang sama dalam pekerjaan dan kedudukan perempuan di dunia kerja sesuai dengan kemampuannya. Implikasi dari penelitian ini adalah Kepemimpinan perempuan bukanlah hal yang tabu, bahkan ada hal positif lain yang tidak ditemukan dalam kepemimpinan atau kinerja laki-laki. Sehingga akan ada perempuan-perempuan lain yang menjadi pemimpin di era modernisasi ini dalam berbagai bidang kerja.